Chemical Composition of Cactus Pear Seed Oil: phenolics identification and antioxidant activity - Berraaouan Ali; Ziyyat Abderrahim; Mekhfi Hassane; Sindic Marianne; Fauconnier Marie-Laure; Legssyer Abdelkhaleq; Aziz Mohammed; Bnouham Mohamed (Korean Pharmacopuncture Institute, 2022)
Objectives: The chemical composition of cactus pear seed oil (Opuntia ficus-indica [L.] Mill.) was analyzed in terms of its fatty acid composition, tocopherol content, phenolic identification, and the oil's phenolic-rich fraction antioxidant power was determined.Methods : : Fatty acid profiling was performed by gas chromatography coupled to an FI detector. Tocopherols and phenolic compounds were analyzed by LC-FLD/UV, and the oil's phenolic-rich fraction antioxidant power was determined by phosphomolybdenum, DPPH assay and β-carotene bleaching test.Results : : Fatty acid composition was marked by a high unsaturation level (83.22 ± 0.34%). The predominant fatty acid was linoleic acid (66.79 ± 0.78%), followed by oleic acid (15.16 ± 0.42%) and palmitic acid (12.70 ± 0.03%). The main tocopherol was γ-tocopherol (172.59 ± 7.59 mg/kg. In addition, Tyrosol, vanillic acid, vanillin, ferulic acid, pinoresinol, and cinnamic acid were identified as phenolic compounds in the analyzed seed oil. Moreover, the oil's phenolics-rich fraction showed a significant total antioxidant activity, scavenged DPPH up to 97.85%, and effectively protected β-carotene against bleaching (97.56%).Conclusion : : The results support the potential use of cactus pear seed oil as a functional food.